2014
DOI: 10.1242/jeb.114116
|View full text |Cite
|
Sign up to set email alerts
|

Does reproduction protect against oxidative stress?

Abstract: A central principle of life-history theory is that parents trade investment in reproduction against that in body maintenance. One physiological cost thought to be important as a modulator of such trade-off is oxidative stress. Experimental support for this hypothesis has, however, proved to be contradictory. In this study, we manipulated the nestling rearing effort of captive canaries (Serinus canaria) soon after the hatching of their nestlings using a brood-size manipulation to test whether an increase in nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 41 publications
3
41
0
Order By: Relevance
“…In fact, females rearing enlarged broods reduced lipid oxidative damage levels, an apparently beneficial effect of reproduction only supported by studies comparing breeding versus non-breeding animals (mostly in female mammals [13]). The only support for this counterintuitive effect in birds come from Costantini et al [14] showing that captive breeding canaries (Serinus canaria) of both sexes endured lower plasma levels of protein and non-protein carbonyls (oxidative damage biomarkers) than birds prevented from reproducing, but not detecting any significant effect from brood size manipulations. A higher OCR in male zebra finches seems to contradict Trivers's theory [49] proposing that females from iteroparous species with biparental care should pay a larger cost from current reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, females rearing enlarged broods reduced lipid oxidative damage levels, an apparently beneficial effect of reproduction only supported by studies comparing breeding versus non-breeding animals (mostly in female mammals [13]). The only support for this counterintuitive effect in birds come from Costantini et al [14] showing that captive breeding canaries (Serinus canaria) of both sexes endured lower plasma levels of protein and non-protein carbonyls (oxidative damage biomarkers) than birds prevented from reproducing, but not detecting any significant effect from brood size manipulations. A higher OCR in male zebra finches seems to contradict Trivers's theory [49] proposing that females from iteroparous species with biparental care should pay a larger cost from current reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental work mostly performed on female rodents (although examples in other species exist) reveals that reproductive effort may even decrease oxidative damage ( [13], in birds [14]). This contrasts with first experiments more than 10 years ago supporting OCR in fruit flies [2,15] and birds (zebra finches, Taeniopygia guttata [3,9]).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in wild animals have found the predicted positive associations between reproduction, daily energy consumption and oxidative damage in lipids and proteins (Bergeron et al, 2011;Heiss and Schoech, 2012;Fletcher et al, 2013;Costantini et al, 2014). Furthermore, studies in wild and captive animals have found evidence of a potential oxidative imbalance resulting from reproduction, including higher production of reactive oxygen metabolites (Casagrande et al, 2012;Stier et al, 2012;Guindre-Parker et al, 2013), decreased antioxidant capacity (Wiersma et al, 2004;Costantini et al, 2010;van de Crommenacker et al, 2011) and diminished resistance to rapid temporary ROS overproduction (Alonso-Alvarez et al, 2004;Bertrand et al, 2006;Losdat et al, 2011;Christe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The idea that oxidative damage (to lipids, proteins, and DNA) is a consequence of reproductive effort has been extensively studied in recent years, but has received mixed support (Blount, Vitikainen, Stott, & Cant, 2016; Metcalfe & Monaghan, 2013; Monaghan, Metcalfe, & Torres, 2009; Selman, Blount, Nussey, & Speakman, 2012; Speakman & Garratt, 2013; Speakman et al., 2015). The general picture from studies on various species is very diverse: from an increase in the oxidative stress during reproduction (Alonso‐Alvarez et al., 2004; Bergeron et al., 2011; Fletcher et al., 2013) through the lack of significant differences between breeders and nonbreeders (Nussey, Pemberton, Pilkington, & Blount, 2009; Vitikainen et al., 2016), to the decrease in oxidative stress in breeding individuals (Costantini, Casasole, & Eens, 2014; Garratt, Pichaud, King, & Brooks, 2013; Garratt et al., 2011; OƂdakowski, Wasiluk, Sadowska, Koteja, & Taylor, 2015; OƂdakowski et al., 2012). …”
Section: Introductionmentioning
confidence: 99%